Unplanned Hospital Visit After Urinary Stone Procedure - Aous Abed AL-Jaleel khaleel; Saad Dakhil Farhan (Diyala Journal of Medicine, 2022)
Background: Urinary stone is a multifactorial disease which is common in daily urological practice, and is also a substantial public health problem. Surgical management of urinary calculi has changed enormously during the past 20 years. Nowadays, the trend among urologists involved in the management of patients with urinary tract stones is to choose the less invasive and more effective option.